2005
DOI: 10.1051/0004-6361:20042355
|View full text |Cite
|
Sign up to set email alerts
|

Probing the outer edge of an accretion disk: a Her X-1 turn-on observed withRXTE

Abstract: We present the analysis of Rossi X-ray Timing Explorer (RXTE) observations of the turn-on phase of a 35 day cycle of the X-ray binary Her X-1. During the early phases of the turn-on, the energy spectrum is composed of X-rays scattered into the line of sight plus heavily absorbed X-rays. The energy spectra in the 3-17 keV range can be described by a partial covering model, where one of the components is influenced by photoelectric absorption and Thomson scattering in cold material plus an iron emission line at … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 34 publications
4
35
0
Order By: Relevance
“…This fits very well within that picture (Schandl & Meyer 1994). This model is also discussed in detail by Kuster et al (2005), who investigated the turn-on of the main-on and find similar columns, although a little bit earlier in the 35 day phase than observation I. We found that the energy of the CRSF does not depend on the 35 day phase, neither in the phase-averaged spectrum nor on the pulse peak data.…”
Section: Day Phase Dependencesupporting
confidence: 89%
See 1 more Smart Citation
“…This fits very well within that picture (Schandl & Meyer 1994). This model is also discussed in detail by Kuster et al (2005), who investigated the turn-on of the main-on and find similar columns, although a little bit earlier in the 35 day phase than observation I. We found that the energy of the CRSF does not depend on the 35 day phase, neither in the phase-averaged spectrum nor on the pulse peak data.…”
Section: Day Phase Dependencesupporting
confidence: 89%
“…The interpulse peak around φ = 0.8 is very weak at this 35 day phase. This is a well known behavior in Her X-1, see, e.g., Scott et al (2000), and has been extensively studied in the literature (see, e.g., Deeter et al 1998;Kuster et al 2005). These energy-resolved pulse profiles are the basis for the phase-resolved spectroscopy described in Section 5.…”
Section: Light Curves and Timingmentioning
confidence: 92%
“…the detection of pulsations. A search for pulsations in the range between 1 s and 10 ks was negative, while shorter period pulsations are probably not detectable due to the smearing of pulsations by Compton scattering (Kuster et al 2005). Turning to the emission lines, we note that our fit requires a slight overabundance of iron with respect to the ISM values of Wilms et al (2000), as one would expect for an evolved star.…”
Section: Discussionmentioning
confidence: 73%
“…The emission measures determined in classical ADC sources such as 4U 1822À37 (Cottam et al 2001), EXO 0748À676 (JimenezGarate et al 2003), 2S 0921À63 (Kallman et al 2003), and Her X-1 (Jimenez-Garate et al 2005) are greater than the ADC model can produce based on the observed luminosity. In the case of Her X-1 it has been suggested that the energy range is indeed much dominated by absorption (Kuster et al 2005;L. Ji et al 2008, in preparation) and the luminosity in its low state may be higher than observed.…”
Section: à3mentioning
confidence: 95%